NONLINEAR BEHAVIOR OF NON-COHESIVE SUBGRADE MATERIALS - Lyapin, Alexandr; Shilyaeva, Olga (Veredas do Direito, 2026)
In the design of highway structures, it is important to take into account the behavior of soil and unbound subgrade layers. The model of nonlinear behavior of bulk materials, in this case sand, was used to describe the behavior of multilayer pavements, specifically the additional base layer. In this study, different variants of the extended Drucker-Prager model were considered to describe the static and dynamic behavior of the elements of a multilayer nonrigid roadway structure.